Analyzing the Effect of Feed-in Tariff and Reserve Margin on Renewable Generation Capacity Expansion - Akhwanzada, Salman A.; Razman, Mat Tahar (IEEE Xplore, 2013)
To meet growing demand, reduce environmental impact, and to attain sustainability in electricity generation, Malaysia is undertaking the task of diversifying the fuel-mix for power generation. In this regard, renewable energy generation has become an important option. It is imperative for the government and private investors to know the possible capacities of renewable energy generation from various sources in order to plan a resilient energy system. In this paper, important factors affecting the development of renewable energy generation are modeled using system dynamics methodology. The variables include feed-in tariff effect, reserves margin, demand growth, and generation capacities. Two renewable sources, solar photovoltaic and municipal solid waste are analyzed from 2012 to 2030. Results show that (1) the maximum installed capacities of solar photovoltaic and municipal solid waste power would reach 1,175.87 MW and 491.59 MW in 2030; (2) from 2013 to 2021, solar power develops rapidly as compared to municipal solid waste, which has the rapid growth between 2017 and 2025; (3)solar power misses its policy target set by the government whereas municipal solid waste surpasses its target;(4)the degression ratio for solar PV has high impact in reducing the capacity additions per year as compared to that of municipal solid waste. These results have important policy implications for long-term energy planning in Malaysia.